Through the water and the storm maritime averages and seaborne trade in early modern Genoa, 1590-1700 - Iodice, Antonio (Mediterranean counterpoints, 2025)
"The maritime legal framework, of General Average (GA), remains an enigmatic and overlooked process within the history of seaborne trade. An ancient rule that predates Roman Law, it continues to be operational today, in a largely unchanged state, mandating the redistribution of unexpected costs that arise during a maritime expedition amongst shipowners and merchants. In this detailed examination of Average procedures within the Italian maritime republic of, Genoa, between the years 1590 and 1700, Through the Water and the Storm demonstrates how this rich data can be used to examine the dynamics of Mediterranean seaborne trade. Drawing on quantitative, socio-economic and legal methodologies, this book highlights how Average procedures reshape our understanding of connectivity and interdependence."